Spatial accessibility of emergency medical services in Chongqing, Southwest China - Zou, Yang; Jia, Ling; Chen, Saijuan; Deng, Xinyi; Chen, Zhiyi; He, Ying; Wang, Qiuting; Xing, Dianguo; Zhang, Yan (Frontiers in Public Health, 2023)
Background: Timely access to emergency medical services (EMS) can significantly reduce mortality. In China, the evidence of the accessibility of complete EMS which considers two related trips and involves large rural areas is insufficient. This study aimed to explore the accessibility of ambulance services and complete EMS in Chongqing and its regional differences, and to provide a reference for improving spatial accessibility of EMS in Chongqing and optimizing allocation of EMS resources. Methods: The nearest neighbor method was used to measure spatial accessibility of ambulance services and complete EMS. Spatial aggregation patterns and influencing factors of spatial accessibility of complete EMS were analyzed using Moran’s I index, Pearson correlation and multiple linear regression. Results: The medians of shortest travel time for ambulance, monitoring ambulance, primary EMS and advanced EMS in Chongqing were 7.0 minutes, 18.6 minutes, 36.2 minutes and 47.8 minutes. The shortest travel time for complete EMS showed significant spatial aggregation characteristics. The Low-Low types that referred to cluster of short EMS travel time mainly distributed in city proper. The High-High types that referred to cluster of long EMS travel time mainly distributed in northeast and southeast of Chongqing. Urbanization rate was a negative influencing factor on shortest travel time for primary EMS, while average elevation and the number of settlements were positive influencing factors. GDP per capita and average elevation were negative influencing factors on shortest travel time for advanced EMS, while the number of settlements was a positive influencing factor. Conclusion: This study evaluated the accessibility of EMS which considers two related trips in Chongqing. Although the accessibility of ambulances in Chongqing was relatively high, the accessibility of monitoring ambulance was relatively low. Regional and urban-rural differences in the accessibility of complete EMS integrating two related trips were obvious. It was recommended to increase financial investment in economic backward areas, increase high-quality EMS resources, enhance EMS capacity of central township health centers, strengthen road construction in mountainous areas, and provide reasonable planning of rural settlements for improving the spatial accessibility of EMS, narrowing the urban-rural gap and improving equity in getting EMS for all the people.